2012
DOI: 10.1002/cmmi.1468
|View full text |Cite
|
Sign up to set email alerts
|

The serial effect of iodinated contrast media on renal hemodynamics and oxygenation as evaluated by ASL and BOLD MRI

Abstract: Contrast-induced nephropathy is a prevalent cause of renal failure, and the mechanisms underlying this injury are not fully understood. We utilized noninvasive functional MRI in order to determine the serial effect of a single administration of iodinated contrast media (CM) on renal hemodynamics and oxygenation. Fifteen rabbits were randomized to receive an intravenous injection of CM (i.e. iopamidol-370; 6 ml kg(-1) body weight) or an equivalent amount of 0.9% saline. Both arterial spin-labeling and blood oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…There is solid experimental evidence that renal ischemia, resulting from an imbalance of various vasodilator and vasoconstrictor factors, is a key factor in the pathogenesis of CI-AKI. 38,[44][45][46] This mechanism causes subsequent ischemia and hypoxia in the renal medulla, a region with extreme susceptibility to ischemic injury. In addition, oxygen free radicals contribute at least in part to the renal tubular cellular injury.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…There is solid experimental evidence that renal ischemia, resulting from an imbalance of various vasodilator and vasoconstrictor factors, is a key factor in the pathogenesis of CI-AKI. 38,[44][45][46] This mechanism causes subsequent ischemia and hypoxia in the renal medulla, a region with extreme susceptibility to ischemic injury. In addition, oxygen free radicals contribute at least in part to the renal tubular cellular injury.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…12,22,42,[55][56][57][58][59] In rats treated with cyclooxygenase and nitric oxide synthase inhibitors, administration of a first-generation ionic hyperosmolar contrast agent reduced medullary oxygenation. 55 Administration of a third-generation nonionic, iso-osmolar, high viscosity contrast agent caused an even greater reduction in medullary oxygenation.…”
Section: Contrast-associated Nephropathymentioning
confidence: 99%
“…55 Administration of a nonionic hyperosmolar contrast agent to rabbits, studied with BOLD MRI, reduced oxygenation of the inner stripe of the outer medulla. 56 In human studies utilizing BOLD MRI (n=10), administration of a second-generation nonionic low osmolar contrast agent reduced medullary oxygenation. 58 In rats and swine studied by BOLD MRI, administration of radiocontrast caused an early and transient increase in medullary T2* followed by a sustained reduction below baseline, with minimal changes observed in the renal cortex.…”
Section: Contrast-associated Nephropathymentioning
confidence: 99%
“…7T), thus resulting in long longitudinal relaxation time (T 1 ) and, therefore, enhanced the sensitivity of ASL techniques. Concerning the ASL scheme strategy, it has been recently demonstrated that, despite modest inversion efficiency, 9 the pCASL approach 2 provides several advantages compared with the widely used pulsed FAIR 14 technique 10,11,13 for mouse kidney perfusion measurement. For the readout strategy, several options are offered, among them EPI (echo planar imaging), RARE (rapid acquisition with relaxation enhancement), TrueFISP (true fast imaging with steady state precession), GRASE (gradient and spin echo), 15 UFLARE (ultra fast low angle rate) 16 or even spiral imaging.…”
mentioning
confidence: 99%
“…S everal studies performed in humans [1][2][3][4][5][6][7][8] and in small animals [9][10][11][12][13] have demonstrated that Arterial Spin Labeling (ASL) MRI can be advantageously used for kidney perfusion studies as it allows quantitative analyses without the need of any exogenous tracer. If the high perfusion level in kidney is an asset for the intrinsically low-sensitive ASL techniques, magnetic field inhomogeneities encountered in the abdomen area along with motion related to respiration strongly challenge ASL measurement quality and robustness.…”
mentioning
confidence: 99%